Web-Based Interest Payment Cashier Information System in Palembang City (Case Study: Latahazanflorisr Plaju Flower Shop) - Inesha Junia Putri Inesha; Karnadi; Dedi Haryanto (Universitas Islam Kuantan Singingi, 2025)
The exiled figure LaTahazan Florisr is a business located in Palal, the city of Palembang. This business is a business that is engaged in ordering flower bouquets, bouquets, flower boards, standing flowers and others. The manual sales system has many drawbacks which are mostly errors in record-keeping, and difficult data search because every time you search for the seller data you have to search in the ledger. To solve these problems, a web-based cashier system is needed. This study adopts an observation method, a literature study using the waterfall method in designing a web-based cashier information system. The system is built and designed to help store admins or cashiers in making sales reports and purchasing calculations easier. The results of this software design are expected to help the work process to be more efficient and can reduce the possibility of calculation errors, and speed up the creation of reports. The designed system describes how each component of the system will work optimally, from managing transaction data to creating ready-to-present sales reports.